Spontaneous Hemopericardium in a Patient Receiving Apixaban Therapy: First Case Report. Issue 7 (10th June 2015) - Sigawy, Chen; Apter, Sara; Vine, Jacob; Grossman, Ehud
<x xml:space="preserve">Abstract</x> Apixaban, a direct factor Xa inhibitor, is a novel oral anticoagulant (NOAC) indicated for prevention of embolic events in patients with nonvalvular atrial fibrillation. The agent is associated with a lower risk of bleeding compared with vitamin K antagonists such as warfarin. Hemopericardium is a life‐threatening bleeding event that is rarely caused by anticoagulants. We describe the case of a 76‐year‐old woman who was diagnosed with nonvalvular atrial fibrillation and treated with apixaban. Six weeks later, she was hospitalized after complaints of weakness and dizziness, and a chest radiograph revealed cardiomegaly. Further imaging, including a computed tomography scan and transthoracic echocardiogram, confirmed a diagnosis of hemopericardium. To our knowledge, this is the first case report of hemopericardium associated with apixaban therapy. This report, along with two previous cases reports of hemopericardium associated with dabigatran and rivaroxaban, emphasizes the need for careful use of NOACs and for further research to identify an antidote or other method for controlling hemorrhage secondary to NOACs in an acute setting. Furthermore, clinicians should consider hemopericardium in the differential diagnosis of patients treated with anticoagulants, including NOACs, who present with cardiomegaly.